PERAN ORANG TUA DENGAN KEJADIAN STUNTING PADA ANAK USIA 3-5 TAHUN DI WILAYAH PUSKESMAS PULO LOR JOMBANG - Hani Rahmawati, Iva Milia; Rosyidah, Inayatur (STIKES dan AKZI Karya Husada Kediri, 2024)
Stunting is a condition in which children experience shorter bodies and are not by their age. Children aged 3-5 years are very at risk of stunting, they must receive support from parents, both physically, psychologically, and nutritionally. The trigger factor that causes stunting is that the role of parents does not run optimally. This study aims to analyze the relationship between the role of parents and the incidence of stunting in the work area of the Pulo Lor Jombang Health Center. Method: This type of research is quantitative research with a cross-sectional approach. The population is mothers who have stunted children aged 3-5 years as many as 60 respondents were taken by random sampling technique and obtained a sample of 52 respondents. The independent variable of this study is the role of parents measured using questionnaires. The dependent variable of this study is the incidence of stunting using observation sheets with data processing editing, coding, scoring, and tabulating. Test statistical analysis with spearmen rank test. Results: The results showed that from 52 respondents there were 2 respondents with good category parental roles (3.8%) and 23 respondents (44.2%) parental roles with sufficient categories (44.2%), while the role of parents with fewer categories amounted to 27 respondents and all experienced stunting events with a total of 52 respondents (100%). The results of the spearmen rank test obtained p value = 0.03 < α 0.05 meaning that H0 rejected and H1 accepted. Conclusion: there is a relationship between the role of parents and the incidence of stunting in children aged 3-5 years in the Pulo Lor Jombang Health Center area. Suggestion: Parents are expected to always improve good parenting patterns including biomedical, mental, and emotional needs.